Modified dynamic gait index and limits of stability in myotonic dystrophy type 1. Issue 5 (23rd September 2018) - Pucillo, Evan M.; Mcintyre, Melissa M.; Pautler, Mary; Hung, Man; Bounsanga, Jerry; Voss, Maren W.; Hayes, Heather; Dibella, Deanna L.; Trujillo, Caren; Dixon, Melissa; Butterfield, Russell J.; Johnson, Nicholas E.
ABSTRACT: Introduction : The purpose of this study was to describe and compare the performance of balance and walking tests in relation to self‐reported fall history in adults with myotonic dystrophy type 1 (DM1). Methods : Twenty‐two (13 male) participants with DM1 completed, a 6‐month fall history questionnaire, the modified Dynamic Gait Index (mDGI), limits of stability (LoS) testing, and 10‐m walking tests. Results : Mean (SD) falls in 6 months was 3.7 (3.1), and 19 (86%) participants reported at least 1 fall. Significant differences in mDGI scores ( P  = 0.006) and 10‐m fast walking gait velocity ( P  = 0.02) were found between those who had been classified as "fallers" and those who had been classified as "nonfallers." Significant correlations were found between mDGI scores and 10‐m walking time. Discussion : Falls are common in DM1, and the mDGI may have potential to distinguish fallers from nonfallers, whereas the LoS failed to detect such impairment. Future studies should further explore use of the mDGI in DM1. Muscle Nerve 58 : 694–699, 2018